Nicotine delivery from the refill liquid to the aerosol via high-power e-cigarette device - Nathalie Prévôt (Nature Portfolio, 2017)
Abstract To offer an enhanced and well-controlled nicotine delivery from the refill liquid to the aerosol is a key point to adequately satisfy nicotine cravings using electronic nicotine delivery systems (ENDS). A recent high-power ENDS, exhibiting higher aerosol nicotine delivery than older technologies, was used. The particle size distribution was measured using a cascade impactor. The effects of the refill liquid composition on the nicotine content of each size-fraction in the submicron range were investigated. Nicotine was quantified by liquid chromatography coupled with tandem mass spectrometry. Particle size distribution of the airborne refill liquid and the aerosol nicotine demonstrated that the nicotine is equally distributed in droplets regardless of their size. Results also proved that the nicotine concentration in aerosol was significantly lower compared to un-puffed refill liquid. A part of the nicotine may be left in the ENDS upon depletion, and consequently a portion of the nicotine may not be transferred to the user. Thus, new generation high-power ENDS associated with propylene glycol/vegetable glycerin (PG/VG) based solvent were very efficient to generate carrier-droplets containing nicotine molecules with a constant concentration. Findings highlighted that a portion of the nicotine in the refill liquid may not be transferred to the user.